Fostering EFL Students’ Academic Literacy: Students' Perception Using Elicit AI - Irwan Sulistyanto; Angga Prasongko; Zidan Maghfiro Tannaka (Edulitics (Education, Literature, and Linguistics) Journal, 2025)
Elicit AI is an artificial intelligence–powered research assistant designed to help users locate, evaluate, and synthesize scholarly sources efficiently. As the use of AI tools in higher education continues to expand, there remains limited empirical research on how such tools are perceived and utilized by English as a Foreign Language (EFL) students, particularly in supporting academic literacy skills such as sourcing and managing references for thesis writing. Addressing this gap, the present study examines English Education students’ perceptions of Elicit AI as a tool for enhancing academic literacy. Using a mixed-method design, data were collected from 21 sixth-semester students through questionnaires and interviews. Results show that 75% of students perceive Elicit AI as useful, 82% find its feedback effective, and 67% report an increase in motivation and engagement. While descriptive data suggest gender neutrality, One-Way ANOVA reveals a significant difference between male and female students. These findings highlight Elicit AI’s potential to foster academic literacy and engagement in EFL contexts. Limitations include the small sample size and reliance on self-reported data. Future research should investigate broader demographics and curriculum-level strategies for the equitable and ethical integration of AI in language education. Overall, Elicit AI demonstrates strong potential as a supplementary tool for fostering academic literacy and supporting students’ engagement in higher education